2020
DOI: 10.1186/s12889-020-08768-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sexual behavior disclosure may distort STI testing outcomes

Abstract: Background: Men who have sex with men (MSM) globally have a high burden of curable sexually transmitted infections (STIs). MSM do not frequently receive rectal STI testing because of several barriers, such as not being out (disclosure of sexual behavior). We evaluate whether Chinese MSM select an STI test (rectal vs urethral) appropriate for their sexual behavior (insertive and/or receptive), and the interactions with being out. Methods: This was a secondary analysis of data from a cross sectional MSM survey c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The HIV testing is correlated with casual sexual behavior [21]. According to our data, people who had HIV test during or before COVID-19 were prone to have casual sexual behavior.…”
Section: Discussionmentioning
confidence: 66%
“…The HIV testing is correlated with casual sexual behavior [21]. According to our data, people who had HIV test during or before COVID-19 were prone to have casual sexual behavior.…”
Section: Discussionmentioning
confidence: 66%
“…Of note, we found that 49% of HIV-infected MSM did not know if they had STIs at the time of HIV-1 diagnosis. Several studies have shown that most persons with syphilis, including up to 44% of MSM, are unaware of their serostatus of syphilis as they may be asymptomatic for years ( 44 , 45 ) or unwilling to disclose their STI diagnosis ( 46 ) and their sexual behaviors ( 15 , 47 ). Our results also showed that MSM without syphilis screening were more likely to be highly connected in the transmission network, indicating that they may have more sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate regression is more appropriate when numerous independent variables are associated with an outcome [ 35 ]. We conform to best practice in previous work in this area, which utilized multivariate regression [ 36 , 37 ]. Similarly, to better understand blocking and its associated covariates, we need to predict blocking instead of investigating it as an exposure which indicates sexual risk or mental health issues.…”
Section: Methodsmentioning
confidence: 99%
“…We adjusted for the following factors and intervention assignment. We decided on these factors based on guidelines established in other studies with the same population [ 36 , 37 ]. We understand the issues around more complex models vs simpler models and have selected the current variables in accordance with best practice as per our previous work in this topic [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation